PENGARUH PERHATIAN ORANG TUA DAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR IPS SISWA DI SDN 130 KARAMBUA DESA RINJANI KECAMATAN WOTU KABUPATEN LUWU TIMUR - Ardillah Abu (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
ABSTRACK This study aims to determine (i) The Effect of Parents' Attention on Social Studies Student Achievement at SDN 130 Karambua. (ii) The Effect of Learning Independence on Social Studies Learning Achievement of Students at SDN 130 Karambua. (iii) Effects of Parental Attention and Learning Independence together on Social Studies Achievement of Students at SDN 130 Karambua, Rinjani Village, Wotu District. This type of research is expost facto. Data analysis used was a simple regression analysis technique for the first and second hypotheses and multiple regression analysis for the third hypothesis. Before analyzing the data, an analysis of the requirements for testing is carried out including: normality, homogeneity, independent t test and linearity test The results of this study are: (i) There is a positive and significant influence of Parents' Attention on Social Studies Student Achievement at SDN 130 Karambua, with rx1y = 0.516; r2x1y = 0.266; and tcount is greater than ttable, namely: 3.85> 1.701. (ii) There is a positive and significant influence of Learning Independence on Social Studies Achievement of Students in SDN 130 Karambua, with rx2y = 0.372; r2x2y = 0.138; and tcount is greater than ttable, namely: 2.119> 1.701. (iii) There is a positive and significant influence of Parental Attention and Learning Independence together on Social Studies Achievement of Students in SDN 130 Karambua, with Ry (1,2) = 0.631; R2y (1,2) = 0.398; and Fcount is greater than Ftable namely: 5.542> 3.35 at a significance level of 5%. The regression line equation Y = 0.615X1 + -0.252X2 + 51.198.